2019
DOI: 10.3390/pathogens8040158
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Leak and Hypercytokinemia Associated with Severe Fever with Thrombocytopenia Syndrome Virus Infection in Mice

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging viral hemorrhagic fever (VHF) endemic to China, South Korea, Japan, and Vietnam. Here we characterize the pathogenesis and natural history of disease in IFNAR-/- mice challenged with the HB29 strain of SFTS virus (SFTSV) and demonstrate hallmark features of VHF such as vascular leak and high concentrations of proinflammatory cytokines in blood and tissues. Treatment with FX06, a natural plasmin digest product of fibrin in clinical development as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Lesions of spleen predominantly consisted of histiocytic and necrotizing splenitis, white pulp atrophy, and diffuse reticuloendothelial hyperplasia of red pulp (Tani et al, 2016;Matsuno et al, 2017;Park et al, 2020). In addition, similar to human severe cases, Westover et al (2019) reported SFTSV-induced vascular fibrinoid necrosis in spleen in Ifnar −/− mice, which was accompanied by increased pro-inflammatory cytokines such as IL-6, monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor (TNFα), IFN-γ, RANTES, and IL-1β in serum, spleen and other tissues. There were pyknosis and karyorrhexis of lymphocytes in both spleen and cervical lymph nodes and histiocytic and necrotizing lymphadenitis lesions in cervical lymph nodes at the late stage of infection (Matsuno et al, 2017).…”
Section: Mitomycin C-treated Micementioning
confidence: 86%
See 1 more Smart Citation
“…Lesions of spleen predominantly consisted of histiocytic and necrotizing splenitis, white pulp atrophy, and diffuse reticuloendothelial hyperplasia of red pulp (Tani et al, 2016;Matsuno et al, 2017;Park et al, 2020). In addition, similar to human severe cases, Westover et al (2019) reported SFTSV-induced vascular fibrinoid necrosis in spleen in Ifnar −/− mice, which was accompanied by increased pro-inflammatory cytokines such as IL-6, monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor (TNFα), IFN-γ, RANTES, and IL-1β in serum, spleen and other tissues. There were pyknosis and karyorrhexis of lymphocytes in both spleen and cervical lymph nodes and histiocytic and necrotizing lymphadenitis lesions in cervical lymph nodes at the late stage of infection (Matsuno et al, 2017).…”
Section: Mitomycin C-treated Micementioning
confidence: 86%
“…In these following studies, Ifnar −/− mice infected with SFTSV exhibited remarkable hematologic changes like severe viremia and leukocytopenia, developed clinical manifestations such as severe weight loss, ruffled fur, and depression, and succumbed to the infection (Tani et al, 2016;Matsuno et al, 2017;Westover et al, 2019;Park et al, 2020). Significant histopathological abnormalities of spleen, liver, kidney, lymph nodes, and bone marrow were common, among which spleen was likely the major target organ with the highest virus titers (Tani et al, 2016;Matsuno et al, 2017;Westover et al, 2019;Park et al, 2020). Lesions of spleen predominantly consisted of histiocytic and necrotizing splenitis, white pulp atrophy, and diffuse reticuloendothelial hyperplasia of red pulp (Tani et al, 2016;Matsuno et al, 2017;Park et al, 2020).…”
Section: Mitomycin C-treated Micementioning
confidence: 93%
“…To prevent the deleterious effects of chronic inflammation, IFN-I during viral infections is important for causing rapid elimination of the virus, thereby curtailing the immune response [2]. For certain viruses, infection of mice that lack expression of IFN-I receptors can lead to heightened pathology associated with elevated production of proinflammatory cytokines [78]. Specifically, IFN-I acts on T effector cells that eliminate virus and regulatory CD4 + T cells that secrete inhibitory cytokines such as IL-10 [79].…”
Section: Systemic Inflammation In Covid-19mentioning
confidence: 99%
“…Additional studies obtained in mice demonstrated a role for type I IFN in the recruitment of proinflammatory cells into the lungs, thus contributing to pathology [ 15 ]. Other mouse models of viral infections have shown that impaired type I IFN response is associated with increased pathology due to the concomitant production of high levels of proinflammatory cytokines [ 16 ]. Supporting this concept, a genetic study has shown that loss of function variants affecting type I IFN response are significantly enriched in patients with life threatening SARS-CoV-2 pneumonia [ 17 ].…”
Section: Dysregulated Type I Ifn Activitymentioning
confidence: 99%